2010
DOI: 10.1111/j.1600-0404.2010.01373.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression predicts unfavourable functional outcome and higher mortality in stroke patients: The Bergen Stroke Study

Abstract: This study has identified several factors associated with PSD. PD predicts more severe stroke on admittance and less functional improvement both in the short- and the long-term. Both PD and PSD predict higher long-term mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 10 publications
6
30
0
Order By: Relevance
“…The Bergen Stroke Study investigators sought to explore the relationship between pre-stroke depression and disability after stroke and demonstrated that pre-stroke depression is associated with increased 6-month disability as measured by the Barthel Index and modified Rankin scale (6). The effect of depression and depressive symptoms on outcome could be mediated by a number of factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Bergen Stroke Study investigators sought to explore the relationship between pre-stroke depression and disability after stroke and demonstrated that pre-stroke depression is associated with increased 6-month disability as measured by the Barthel Index and modified Rankin scale (6). The effect of depression and depressive symptoms on outcome could be mediated by a number of factors.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of depression and depressive symptoms on outcome could be mediated by a number of factors. Pre-stroke depression predicts development of post-stroke depression which is related to stroke outcome (6). Depressive symptoms may impact behaviors such as willingness to participate in rehabilitation, thereby limiting improvements in function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…diet and exercise) to prevent recurrence, and assertiveness in seeking acute medical care. Depression may influence the association of these psychological factors with stroke outcome as depression is clearly associated with stroke outcome 5 and is also associated with these psychological factors 6, 7, 8 . Depression has also been linked to vascular disease pathophysiology 9 .…”
Section: Introductionmentioning
confidence: 99%
“…[6] Only a few studies consider overall impact of the factor on the prognosis of patients. However, due to low viscosity of rehabilitation patients, the samples of existing studies generally in a single hospital, a single area, it is difficult to follow the actual follow-up of patients with hospital conditions caused by the results of bias.…”
Section: Introductionmentioning
confidence: 99%